ChemInform Abstract: Synthesis, Structure, and Na‐Ion Migration in Na4NiP2O7F2: A Prospective High Voltage Positive Electrode Material for the Na‐Ion Battery. Issue 17 (April 2015) - Kundu, Dipan; Tripathi, Rajesh; Popov, Guerman; Makahnouk, W. R. M.; Nazar, Linda F.
Abstract Single crystals of Na4NiP2O7F2 are prepared by a flux reaction of NiO with excess Na2PO3F (Au crucible in silica tube, 675 °C, 8 h; cooling to 400 °C within 10 h).